The Effect Of Muḍārabah Financing And Musyārakah Financing On Operational Revenue Of Sharia People Financing Bank (BPRS In Indonesia 2014-2018 Period) - mariati mariati; abdul nasser hasibuan; idris saleh; fauzan fauzan (Journal Of Sharia Banking, 2021)
Based on the financial report data of Muḍārabah financing, Musyārakah, and operating income in the Islamic People's Financing Bank in 2014 to 2018. An increase in financing but not followed by an increase in operating income, and also vice versa operating income has increased but the funding has decreased. So that the formulation of the problem in this research is whether there is an influence of Murārabah financing and Musyārakah financing on operational income at the Islamic People's Financing Bank. With the aim of this study is to determine the effect of Muḍārabah financing and Musyārakah financing partially and simultaneously on operational income at the Islamic People's Financing Bank. The discussion of this study relates to Muḍārabah financing and Musyārakah financing and operational income of the Islamic People's Financing Bank (BPRS) and is complemented by other sciences related to the topic under study. This research is a quantitative study, using secondary data and time series forms from 2014 to 2018 as many as 60 samples. Data analysis used was descriptive statistical analysis test, normality test, classic assumption test (multicollinearity test, heteroscedasticity test, autokoleration test), R2 test, hypothesis test (t test, F test), and multiple linear regression tests with processing used through SPSS 23. Partial research results (t-test) There is no effect of Muḍārabah financing on operating income at the Islamic People's Financing Bank in Indonesia for the 2014-1018 period. There is an influence of Musharaka financing on the operational income of Islamic People's Financing Banks in Indonesia for the 2014-2018 period. While simultaneous Fcount has a value greater than Ftable, this explains that Muḍārabah financing and Musyārakah financing have a significant simultaneous effect on operational income.